Marchandises Montevideo. (Antwerpen : Montevideo, 1983)
Van Den Abbeele, Wim ; van Bergen, Thé ; Bervoets, Fred ; Beyns, Freddy ; Bijl, Guillaume ; Bruneau ; Castelyns, Frank F. ; Cox, Jan ; Debbaut, Charles ; Deleu, Luc ; Free, W.J.C. ; Gentils, Frans ; Gentils, Paul ; Ghekiere, Joris ; Van Goethem, Nicole ; Goossens, Walter ; Van Haevre, Johan ; Huet, Wilfried ; Jacobs, Herman ; Jacobs, Tin ; Jambers, Mark ; Janssens, Hugo ; Janssens, Jan ; Van Kerckhoven, Anne-Mie ; Kortekaas, Niek ; Lens, Ludo ; M-Bryd ; van Maele, Marcel ; Meeus, Lieve ; Michel, Johnny ; Morez, Paul ; Pacquée, Ria ; Pas, Wilfried ; Peeters, Gisele ; Radio Centraal ; Van Ravels, Thérèse ; Roelandt, Hugo ; Rombouts, Guy ; Van Roosmaelen, Frans ; van Rooy, Walter ; Schepers, Marc ; Van Soom, Luc ; Steculorum, Leo ; van Steen, Rob ; Szukalski, Albert ; Teller, Christine ; Tielemans, Willy ; V-Deckers, Jurgen ; Verbist, Luc ; Vercammen, Wout ; Verelst, Patrick ; Verleyen, Jan ; Vertessen, Liliane ; Vossen, Elie ; De Vylder, Proj ; Weinberger, Daniël ; Wiggers, Harry ; Wilms, Jos ; Ysbrandt ; Wuytack, Louis
Nederlands
Marchandises Montevideo, Montevideo, Antwerpen, verschillende locaties, 14.04.1983 - 24.04.1983
boek